THE IMPORTANCE OF PACKAGING ATTRIBUTES OF TAKE-OUT FOOD: A CONJOINT ANALYSIS APPROACH - Widaningrum, Dyah Lestari (Industrial and Systems Engineering Assessment Journal (INASEA), 2013)
This research aimed to investigate the importance of take-out food packaging attributes, using conjointÂ analysis approach among consumers of take-out food products in Jakarta, Indonesia. The conjoint resultsÂ indicated that perception about packaging materials (such as paper, plastic, and polystyrene foam) took theÂ most important role in overall consumer perception. The clustering results showed that there were strongÂ segmentations for take-out food packaging material considered most important by consumers. Some consumersÂ were mostly oriented to the colour of packaging, while some concerned on packaging shape and packagingÂ information. Segmentation variables based on packaging response could provide very useful information toÂ maximize image of products through the packageâs impact